Abuse and Intentional Misuse of Promethazine Reported to US Poison Centers. Issue 3 (May 2015) - Tsay, M. Ellen; Procopio, Gabrielle; Anderson, Bruce D.; Klein-Schwartz, Wendy
<x xml:space="preserve">Abstract</x> Objective: Promethazine abuse has been reported. The objective was to investigate promethazine abuse/misuse in the United States. Methods: An 11-year retrospective review was conducted of promethazine abuse and intentional misuse cases without co-ingestants in persons 10 years and older reported to the National Poison Data System. Data were stratified by product (promethazine-alone [PA] or co-formulation [PC]) and evaluated for demographics, toxicity, management sites, and outcomes. Results: There were 354 single product abuse or misuse exposures—95 PA and 259 PC. Over the 11-year timeframe, the annual exposure rate per 100, 000 population doubled. Exposures were most prevalent among 10 to 19 years old and young adults (20s), accounting for 69.5% of PA and 57.5% of PC cases. Clinical effects due to PA included drowsiness (43.2%), tachycardia (7.4%), agitation (13.7%), confusion (13.7%), slurred speech (12.6%), hallucinations (7.4%), dizziness (7.4%), and hypertension (5.3%). Drowsiness (53.4%) and tachycardia (20.8%) were more frequent with PC. There were significant differences between PA and PC in management site (P = 0.0078). Management sites for PA and PC, respectively, were emergency department (37.9%, 55.6%), non–health care facility (33.7%, 14.7%), critical care unit (8.4%, 11.2%), non–critical care unit (7.4%, 7.3%), psychiatry (2.1%, 4.2%), and other/unknown (10.5%, 7.0%). Outcomes for PA and PC, respectively, were no effect (21.0%, 12.4%), minor (58.9%, 53.7%), moderate (17.9%, 32.0%), and major effects (2.1%, 1.9%). Conclusions: Promethazine-alone abuse/misuse most frequently resulted in minor outcomes, and less than 20% required medical admission. Abuse/misuse of PC resulted in a higher frequency of health care facility treatment and a trend toward more moderate outcomes. These differences are most likely attributed to the co-formulate.